Animal Waste Management Become Compost and Straw Fermentation Technology in Sumberejo Mranggen Demak Central Java - Fuskhah, Eny (Talenta Publisher Universitas Sumatera Utara, 2019)
The problem experienced by farmer groups in Sumberejo Village, Mranggen Subdistrict, Demak Regency was that it had not managed well the manure that exists to mount beside the cage, the difficulty of providing forage / grass especially in the dry season and the length of time counting grass for livestock, so farmers often provide just the grass or straw he got. Even if the grass was enumerated before being given livestock, it would increase the digestibility so that it would add value to the livestock. The solutions offered were education and counseling for the processing of livestock waste into compost, efforts to utilize rice and corn straw with fermentation technology, and efforts to improve cattle feed by using grass chopping tools.